RISKS OF SURGICAL TREATMENT OF SECONDARY HYPERPARATHYROIDISM IN PATIENTS WITH CHRONIC RENAL FAILURE - Tkachenkо, R.P.; Gubar, O.S. (World of Medicine and Biology, 2013)
Early diagnosis of secondary hyperparathyroidism in patients with chronic renal failure will permit to avoid the unjustified delay of surgical treatment, to decrease the risk of complication and to improve patient quality of life and life span. Surgical treatment VHPT allow time to avoid irreversible severe complications of long-existing pathology and assess the prospects for treatment, including kidney transplant.
Keywords: secondary hyperparathyroidism; diagnosis; surgery